2021
DOI: 10.1002/cam4.3814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative TACE on incidences of microvascular invasion and long‐term post‐hepatectomy survival in hepatocellular carcinoma patients: A propensity score matching analysis

Abstract: Background To study the influence of preoperative transcatheter arterial chemoembolization (TACE) on the incidence of microvascular invasion (MVI) and long‐term survival outcomes in hepatocellular carcinoma (HCC) patients. Methods Between January 1, 2010 and December 1, 2014, consecutive HCC patients who underwent curative liver resection were enrolled in this study. Univariable and multivariable regression analyses were used to identify independent predictive factors of MVI. Propensity score matching (PSM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The results showed that preoperative TACE had no effect on the incidence of MVI. Meanwhile, their results also showed that preoperative TACE had little influence on the DFS and OS of HCC patients after liver resection [ 20 ].…”
Section: The Comprehensive Management Of Microvascular Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that preoperative TACE had no effect on the incidence of MVI. Meanwhile, their results also showed that preoperative TACE had little influence on the DFS and OS of HCC patients after liver resection [ 20 ].…”
Section: The Comprehensive Management Of Microvascular Invasionmentioning
confidence: 99%
“…However, Lee et al [ 18 , 19 ] reported that anatomical resection could not improve the prognosis for patients with HCC >2 cm with MVI. Moreover, Yang et al pointed out that preoperative TACE had no effect on the incidence of MVI [ 20 ]. But Chen et al found that postoperative adjuvant TACE were beneficial for those HCC patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that postoperative TACE can effectively reduce the aggressiveness of microvascular invasion, thereby reducing recurrence. [ 63 65 ] Yang et al [ 52 ] reported that preoperative TACE may achieve a similar effect on patients. Furthermore, Wang et al [ 66 ] strongly recommended preoperative TACE in patients with HCC exhibiting microvascular invasion and reported that preoperative TACE could benefit patients with “middle risk” according to the current staging systems.…”
Section: Screening Of Subgroups Of Patients Who Benefit From Preoperative Tacementioning
confidence: 99%
“…[28] Sciarra et al [43] found that up to 60% of patients with HCC who underwent TACE did not benefit from the treatment despite multiple sessions. In addition, a subsequent meta-analysis largely did not support a survival benefit of routine preoperative TACE for all patients undergoing SR of HCC [16,[44][45][46][47][48][49][50][51][52] [Table 1]. These findings suggest that TACE might have a positive effect on certain subgroups of patients with resectable HCC.…”
Section: Detrimental Effects Of Preoperative Tacementioning
confidence: 99%
“…However, for HCC patients with large hepatocellular carcinoma (> 5 cm), the tumor is highly malignant and prone to recurrence after surgery, with the vast majority of patients eventually dying due to tumor recurrence ( 4 ). This creates an urgent need for appropriate treatment measures to control postoperative recurrence of HCC ( 5 ).…”
Section: Introductionmentioning
confidence: 99%